A focus on different factors affecting hydrogen induced cracking in oil and natural gas pipeline steel. (September 2017) - Mohtadi-Bonab, M.A.; Eskandari, M.
Abstract: In this research, hydrogen induced cracking (HIC) behavior of an API X70 pipeline steel has been studied. In order to create HIC cracks, an electrochemical hydrogen charging experiment was carried out on X70 steel by using 0.2 M sulfuric acid and 3 g/l ammonium thiocyanate for 8 h. Moreover, SEM, EDS and EBSD techniques were used to characterize the as-received (AR) steel and investigate the different aspects of HIC phenomenon as well. The results showed that the inclusions and precipitates which play a key role in HIC phenomenon have been distributed randomly through the cross-section of tested steel. However, the concentration of them was higher at the center of cross-section than other areas. All HIC cracks initiated and propagated through the center of thickness where center segregation of elements has occurred. It is also observed that HIC cracks were initiated from several special types of inclusions and precipitates such as manganese sulphide and carbonitride precipitates. EBSD results showed that the dominant local texture of center of thickness in RD-TD plane was 001//ND and 111//ND. Moreover, HIC cracks propagate through differently oriented grains where the local texture is random. Highlights: Susceptibility of X70 pipeline steel to hydrogen induced cracking was studied. Different types of inclusions in as-received X70 steel were found. The results showed that inclusions were randomly distributed in the cross-section of tested specimens. Manganese sulphide and carbonitride precipitates were found to be harmful for HIC phenomenon. Role of micro-texture parameters on HIC was studied by EBSD measurements.